Coach development in New Zealand - Kidman, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
In New Zealand, a paradigm shift in coach development and education has been instigated, whereby athletes are the focus (Kidman, 2005; Lombardo, 2002). The traditional `scientised` paradigm in coach development (Kidman and Davis, 2007) is gradually being shifted to providing a quality service to athletes through further developing coaches on the `how and who` of coaching. The new paradigm for coach development comes in the form of a New Zealand Coach Development Framework, published in 2006 by Sport and Recreation New Zealand (SPARC).